Adapting and Operationalizing the RE-AIM Framework for Implementation Science in Environmental Health: Clean Fuel Cooking Programs in Low Resource Countries - Quinn, Ashlinn K.; Neta, Gila; Sturke, Rachel; Olopade, Christopher O.; Pollard, Suzanne L.; Sherr, Kenneth; Rosenthal, Joshua P. (Frontiers in Public Health, 2019)
Introduction: The use of models and frameworks to design and evaluate strategies to improve delivery of evidence-based interventions is a foundational element of implementation science. To date, however, evaluative implementation science frameworks such as Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) have not been widely employed to examine environmental health interventions. We take advantage of a unique opportunity to utilize and iteratively adapt the RE-AIM framework to guide NIH-funded case studies of the implementation of clean cooking fuel programs in eleven low- and middle-income countries. Methods: We used existing literature and expert consultation to translate and iteratively adapt the RE-AIM framework across several stages of the NIH Clean Cooking Implementation Science case study project. Checklists and templates to guide investigators were developed at each stage. Results: The RE-AIM framework facilitated identification of important emerging issues across this set of case studies, in particular highlighting the fact that data associated with certain important outcomes related to health and welfare are chronically lacking in clean fuel programs. Monitoring of these outcomes should be prioritized in future implementation efforts. As RE-AIM was not originally designed to evaluate household energy interventions, employing the framework required adaptation. Specific adaptations include the broadening of Effectiveness to encompass indicators of success toward any stated programmatic goal, and expansion of Adoption to include household-level uptake of technology. Conclusions: The RE-AIM implementation science framework proved to be a useful organizing schema for eleven case studies of clean fuel cooking programs, in particular highlighting areas requiring emphasis in future research and evaluation efforts. The iterative approach used here to adapt an implementation science framework to a specific programmatic goal may be of value to other multi-country program efforts, such as those led by international development agencies. The checklists and templates developed for this project are publicly available for others to use and/or further modify.